Antarctic Thraustochytrids as Sources of Carotenoids and High-Value Fatty Acids - Allison Leyton; Liset Flores; Carolina Shene; Yusuf Chisti; Giovanni Larama; Juan A. Asenjo; Roberto E. Armenta (Marine Drugs, 2021)
Eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and carotenoids are needed as human dietary supplements and are essential components in commercial feeds for the production of aquacultured seafood. Microorganisms such as thraustochytrids are potential natural sources of these compounds. This research reports on the lipid and carotenoid production capacity of thraustochytrids that were isolated from coastal waters of Antarctica. Of the 22 isolates, 21 produced lipids containing EPA+DHA, and the amount of these fatty acids exceeded 20% of the total fatty acids in 12 isolates. Ten isolates were shown to produce carotenoids (27.4–63.9 μg/g dry biomass). The isolate RT2316-16, identified as Thraustochytrium sp., was the best producer of biomass (7.2 g/L in five days) rich in carotenoids (63.9 μg/g) and, therefore, became the focus of this investigation. The main carotenoids in RT2316-16 were β-carotene and canthaxanthin. The content of EPA+DHA in the total lipids (34 ± 3% w/w in dry biomass) depended on the stage of growth of RT2316-16. Lipid and carotenoid content of the biomass and its concentration could be enhanced by modifying the composition of the culture medium. The estimated genome size of RT2316-16 was 44 Mb. Of the 5656 genes predicted from the genome, 4559 were annotated. These included genes of most of the enzymes in the elongation and desaturation pathway of synthesis of ω-3 polyunsaturated fatty acids. Carotenoid precursors in RT2316-16 were synthesized through the mevalonate pathway. A β-carotene synthase gene, with a different domain organization compared to the gene in other thraustochytrids, explained the carotenoid profile of RT2316-16.